Successful post-term pregnancy in scared bicornuate uterus: case report - Tebabere Moltot; Tesfanesh Lemma; Mulualem Silesh; Moges Sisay; Birhan Tsegaw (BMC, 2023)
Abstract Pregnancies in the bicornuate uterus are usually considered high-risk because of their association with poor reproductive outcomes such as recurrent pregnancy loss, cervical insufficiency, low birthweight, preterm birth, malpresentation, cesarean delivery, and uterine rupture. The objective of the report was to show that patients with a scared bicornuate uterus at post-term could have successful pregnancy outcomes. We are presenting a 28-year-old gravida III para II lady with a bicornuate scared uterus at post-term. She has a history of early third-trimester pregnancy loss, and her second pregnancy was delivered via cesarean section. In her first pregnancy, the patient's uterus was not identified as bicornuate. However, an ultrasound during her second pregnancy revealed that she had a bicornuate uterus, which led to the diagnosis. At term, the lady had a successful cesarean section. Lastly, for the current post-term pregnancy she had no prenatal check-up. Even though this, she was coming at the latent first stage of labor and an emergency cesarean section was done. Conclusion Successful outcomes could be achieved in patients with the bicornuate uterus at post-term gestation.